-7-x=1+x

Simple and best practice solution for -7-x=1+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-x=1+x equation:


Simplifying
-7 + -1x = 1 + x

Solving
-7 + -1x = 1 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-7 + -1x + -1x = 1 + x + -1x

Combine like terms: -1x + -1x = -2x
-7 + -2x = 1 + x + -1x

Combine like terms: x + -1x = 0
-7 + -2x = 1 + 0
-7 + -2x = 1

Add '7' to each side of the equation.
-7 + 7 + -2x = 1 + 7

Combine like terms: -7 + 7 = 0
0 + -2x = 1 + 7
-2x = 1 + 7

Combine like terms: 1 + 7 = 8
-2x = 8

Divide each side by '-2'.
x = -4

Simplifying
x = -4

See similar equations:

| -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 | | 2-(6x-19)=7(x-2) | | 6x=6(x+5)+6 | | 4x-8=4x+9 | | 4=-2x+36 | | 7.4x-1.1=13.7 | | 3x^2+9x-44=0 | | 4(x+6)=21 | | 8(6)+9y=36 | | 12x-4(5+3x)=20 | | c=3+2x | | 5(2c+3d)-8d= | | 2+3x=14+6x | | 2e^3x-8=32 | | 3(6z-1)-5(z+7)=8(z+1) | | -6+3y=-24 | | 9x+18=11x-12 | | 80x^3-60x^2=0 | | 2a^2x^2+x-2a^2b^2x-b^2=0 | | 4x^2-4x^2-x^2+1=0 | | x^2+7x-.75=0 | | 4-3n=8-6n |

Equations solver categories